A Huge Malignant Gastric Gastrointestinal Stromal Tumor in a Young Patient - Jeong, Yun Jin; Hwang, Hyun Seung; Park, Yong Eun; Nam, Kyung Han; Oh, Sung Jin (The Korean journal of gastroenterology, 2022)
Malignant gastrointestinal stromal tumors (GISTs) are rare neoplasms originating from the gastrointestinal tract that rarely occur in patients below 40 years of age. To our knowledge, there have been no previous reports of satellite and metastatic nodules in GIST. We present a case of a young patient with a huge malignant gastric GIST accompanied by spontaneous bleeding and satellite and metastatic nodules, successfully treated surgically, without preoperative chemotherapy administration. A 28-year-old man was admitted to Haeundae Paik Hospital with melena. A huge bulging gastric mass with ulceration and bleeding was observed on endoscopy. A subepithelial lesion on the stomach body, abutting the pancreatic body and tail, with regional lymph node enlargement was confirmed by EUS and CT. Radical total gastrectomy was performed, the invasion surrounding the pancreatic tail and spleen were surgically dissected, and enlarged lymph nodes around the celiac trunk and the common hepatic artery were removed. The pathology results showed a malignant GIST with two satellite nodules and a metastatic tumor nodule at the left paracardial lymph node site. After complete resection of the malignant GIST, adjuvant chemotherapy with imatinib was initiated. Follow-up CT and endoscopy performed 6 months after surgery confirmed no recurrence of the disease.